2011
DOI: 10.1038/nbt.1742
|View full text |Cite
|
Sign up to set email alerts
|

Efficient mucosal vaccination mediated by the neonatal Fc receptor

Abstract: Vaccine strategies to prevent invasive mucosal pathogens are being sought because 80–90% of infectious diseases are initiated at mucosal surfaces. However, our ability to deliver an intact vaccine antigen across a mucosal barrier for induction of effective immunity is limited. The neonatal Fc receptor (FcRn) mediates the transport of IgG across polarized epithelial cells lining mucosal surfaces. By mimicking IgG transfer at mucosal surfaces, intranasal immunization with a model antigen, herpes simplex virus ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
160
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(168 citation statements)
references
References 42 publications
6
160
0
2
Order By: Relevance
“…Our findings indicate that endosomal or phagosomal FcRn in both DCs and Mfs protects ICs from rapid catabolism and leads to optimal Ag processing for the final stage of loading peptides onto the MHC class II molecule. In addition to revealing FcRn activities in IgG protection and transcytosis (7), our data further expand our understanding of immune function by demonstrating an additional function for the FcRn in Ag presentation, which may also help us better understand the mechanisms of FcRn-targeted systemic or mucosal immunizations (57,58). The results presented thus far favor a model in which ICs internalized within endosomes or phagosomes through FcgR-mediated processes that promote FcgR-IC binding activity at the cell surface switch to FcRn-IC binding when the internal environment becomes acidic (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that endosomal or phagosomal FcRn in both DCs and Mfs protects ICs from rapid catabolism and leads to optimal Ag processing for the final stage of loading peptides onto the MHC class II molecule. In addition to revealing FcRn activities in IgG protection and transcytosis (7), our data further expand our understanding of immune function by demonstrating an additional function for the FcRn in Ag presentation, which may also help us better understand the mechanisms of FcRn-targeted systemic or mucosal immunizations (57,58). The results presented thus far favor a model in which ICs internalized within endosomes or phagosomes through FcgR-mediated processes that promote FcgR-IC binding activity at the cell surface switch to FcRn-IC binding when the internal environment becomes acidic (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 This property has been successfully exploited for pulmonary delivery, as well as intranasal immunization with Fc-fusion proteins. 17,18 Lastly, FcRn was also reported to transport IgGantigen complexes, thus favoring antigen-presentation, [19][20][21] and to enable phagocytosis of IgG-opsonized bacteria by neutrophils, 22 demonstrating a wide range of functions for this receptor in several immunological and non-immunological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated this principle by immunization of mice with a Fc-fusion protein that consisted of herpes simplex virus type-2 glycoprotein gD, which led to the generation of protective antibodies that prevented subsequent intravaginal infection of a virulent HSV-2 strain. 39 The multi-functioning roles of FcRn in different tissues appear to coordinate adaptive immunity, and this process appears to be a rational strategy for vaccine development in the prevention of mucosal infections.…”
mentioning
confidence: 99%
“…37 Recent studies showed that FcRn in the vaginal epithelium, similar to that of intestine, can mediate bidirectional transport of IgG and secretion of IgG for immune protection. 38,39 Liver. FcRn in the liver is the major site for the maintenance of albumin homeostasis.…”
mentioning
confidence: 99%